Enhancement of welding strength through electric current and resistance on ERSW process using chromium steel. (2020) - Radhika, A.; Thenmozhi, G.; Balakarthikeyan, M.; Stalin, B.
Abstract: Welding technology is an important concept in every industry. The electric resistance welding is recently used in marine, automotive, and boiler. In the present study, the effect of various factors such as welding current, weld time, and electrode force against the strength of weld in Electric Resistance Seam Welding (ERSW). The quality of the chromium welded joints depends on current and electric resistance. Taguchi parametric optimization and contour plot analysis is used to investigate the experimental results. The factor involvement is evaluated through variance analysis.